Cancer specialist nurses' experiences of supporting family members of persons diagnosed with colorectal cancer: A qualitative study. (December 2022) - Samuelsson, Maria; Jakobsson, Jenny; Wennick, Anne; Lydrup, Marie-Louise; Bengtsson, Mariette
Abstract: Purpose: The purpose of the present study was to explore cancer specialist nurses' experiences of supporting family members of persons diagnosed with colorectal cancer. Method: The study was designed as a qualitative study. Data was collected using individual semi-structured telephone interviews with 21 cancer specialist nurses. The interviews were transcribed and analysed with reflexive thematic analysis. Results: The analysis generated one overarching theme, In the shadow of the person diagnosed with colorectal cancer, and four themes: striving for confidence, searching for ways to support, seeking individualization, and balancing between needs. Swedish colorectal cancer care is organized with the persons diagnosed with colorectal cancer as the centre of care and lacks both structure and allocated resources for supportive care for family members. Thus, support for family members has to be provided within the existing colorectal cancer care. The support provided focuses mainly on strengthening the family members' ability in the caregiving role and is offered primarily at the time of diagnosis. Conclusion: There is an apparent need for developing supportive care plans for family members, involving repeated assessments of multidimensional needs, a tailored support, and follow-ups. Accordingly, a re-evaluation of the cancer specialist nurse's role is needed so that key nursing responsibilities are not ranked second to administrative tasks. Highlights: Family members of persons diagnosed with cancer also have supportive care needs. Allocated resources for supportive care for family members are missing. The support provided to family members focuses mainly on their caregiving role. Support is offered primarily at the time of diagnosis. Possibilities for a structured needs assessment are lacking.